2013
DOI: 10.5101/nml.v5i2.p88-92
|View full text |Cite
|
Sign up to set email alerts
|

Nano brazing of Pt-Ag nanoparticles under femtosecond laser irradiation

Abstract: Nano brazing of Pt-Ag nanoparticles with nano Ag filler metal is reported in this letter, which presents an effective way to join nanoobjects by femtosecond laser irradiation. The nano brazed interface between Pt-Ag and Ag showed good lattice matching along (111)Ag//(111)Ag-Pt. Lattice mismatch can hardly be observed at the interface between the filler metal and Pt-Ag nanoparticle, which is important for the joint strength and normally does not occur during joining. The very low mismatch also suggested that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The direction of polarization of laser was found to be an important factor affecting the plasmon excitation when irradiating Ag NWs 188 . Ag filler materials were studied for fs laser joining of Pt-Ag alloy NPs in an aqueous solution, it was found that the lattices between Ag and Pt-Ag showed a good matching along(111) planes, which might be due to a melting and solidification during joining process189 . When PVP coated Ag NPs were irradiated by fs laser in solution, the radiation could graphitize the PVP layer and change the surface condition of Ag NPs to increase the surface diffusion for joining of Ag NPs, seeFigure 17a-b.…”
mentioning
confidence: 99%
“…The direction of polarization of laser was found to be an important factor affecting the plasmon excitation when irradiating Ag NWs 188 . Ag filler materials were studied for fs laser joining of Pt-Ag alloy NPs in an aqueous solution, it was found that the lattices between Ag and Pt-Ag showed a good matching along(111) planes, which might be due to a melting and solidification during joining process189 . When PVP coated Ag NPs were irradiated by fs laser in solution, the radiation could graphitize the PVP layer and change the surface condition of Ag NPs to increase the surface diffusion for joining of Ag NPs, seeFigure 17a-b.…”
mentioning
confidence: 99%